2010
DOI: 10.4049/jimmunol.0902103
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Release from the Endoplasmic Reticulum of NY-ESO-1–Specific T Cells Is Modulated by the Affinity of TCR and by the Use of the CD8 Coreceptor

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 68 publications
4
35
0
Order By: Relevance
“…3b). These results are consistent with previously published data showing that recognition of a strong agonist ligand results in a very rapid onset and fast accumulation of intracellular Ca 2+ , while stimulation with weak agonists significantly delays the onset time and induces much slower accumulation of intracellular Ca 2+ with lower average magnitude1213. Furthermore, the delay of the onset time revealed a poor dependence on the peptide concentration12.…”
Section: Resultssupporting
confidence: 92%
“…3b). These results are consistent with previously published data showing that recognition of a strong agonist ligand results in a very rapid onset and fast accumulation of intracellular Ca 2+ , while stimulation with weak agonists significantly delays the onset time and induces much slower accumulation of intracellular Ca 2+ with lower average magnitude1213. Furthermore, the delay of the onset time revealed a poor dependence on the peptide concentration12.…”
Section: Resultssupporting
confidence: 92%
“…The relationship between TCR-pMHC interaction kinetics and intracellular signaling to cytotoxic granule release was recently clarified in a study that observed efficient centrosome polarization but a decrease in granule recruitment in response to a shorter TCR-pMHC interaction (59). Lower-affinity pMHC ligand also correlates with less cytotoxic granule polarization in tumor-reactive T cells (33). In vivo, studies varying the amount of Ag showed a correlation between pMHC density and CD8 + cytotoxic function (44,60).…”
Section: Tcr-pmhc Interaction Parameters and In Vivo T Cell Immunitymentioning
confidence: 99%
“…Increase in the concentration of intracellular Ca 2+ occurs with a delay after a shorter TCR-pMHC interaction (31) or a lower dose of pMHC ligand (32). A recent study of Ca 2+ dynamics in tumor-reactive T cells showed that a high-affinity pMHC ligand induced sustained Ca 2+ flux and emptying of endoplasmic reticulum Ca 2+ stores, but oscillating Ca 2+ flux and only partial endoplasmic reticulum emptying was observed with a lower-affinity ligand during the time frame examined (33). In addition, recruitment of CD3z to the T cell-APC synapse was delayed in response to a pMHC ligand with a shorter TCR interaction, but normal levels of accumulation (as seen with natural pMHC ligand) were achieved after twice as much time had elapsed (34).…”
Section: Tcr-pmhc Binding Parameters: Definitions and Controversiesmentioning
confidence: 99%
“…The affinity of a TCR to a given peptide epitope is dependent on its TCR sequence, which impacts the downstream fate (2) and functional capacity (3) of T cells by modulating TCR signaling strength (4) and proliferation rates (3, 5). TCR-pMHC affinity is widely known to be a major determinant in the efficacy of adoptive T cell transfer therapy (ACT).…”
Section: Introductionmentioning
confidence: 99%